Design of a microalgae bio-reactive facade reactor for cultivation of Chlorella vulgaris (2017)
The increasing global demand for energy that has existed during many decades has affected the environment due to the greenhouse gas emissions, which are the result of the inadequate use of fossil fuels. This situation has contributed to the development of researchers regarding the microalgae production to capture the CO2 present in the atmosphere. Therefore, this paper presents the influence of the design variables (width and depth) of a flat-plate photobioreactor on the biomass productivity of Chlorella vulgaris UTEX 1803 and the evaporated volume for a period of 74 days, under the environmental conditions of Bucaramanga, Colombia. In addition, the effect of evaporated volume and temperature on biomass productivity was analyzed. It was verified that the average temperature of 29.72 °C is not an influential variable on biomass productivity. According to the results, the design of a photobioreactor with width dimensions greater than 15 cm and depth 3 cm is required to obtain a productivity of 0.35 g/L d.